Stomatal regulation of DPV in yerba mate (Ilex paraguariensis) under different levels of shades in Misiones, Argentina - Bulfe, Nardia María; Gonzalez, Paola Analia; Barth, Sara Regina (Sociedad Argentina de Fisiología Vegetal, 2025)
Poster